Disruption of adenosine 2A receptor exacerbates NAFLD through increasing inflammatory responses and SREBP1c activity. Issue 1 (10th May 2018) - Cai, Yuli; Li, Honggui; Liu, Mengyang; Pei, Ya; Zheng, Juan; Zhou, Jing; Luo, Xianjun; Huang, Wenya; Ma, Linqiang; Yang, Qiuhua; Guo, Shaodong; Xiao, Xiaoqiu; et al.
Abstract : Adenosine 2A receptor (A2A R) exerts protective roles in endotoxin‐ and/or ischemia‐induced tissue damage. However, the role for A2A R in nonalcoholic fatty liver disease (NAFLD) remains largely unknown. We sought to examine the effects of global and/or myeloid cell‐specific A2A R disruption on the aspects of obesity‐associated NAFLD and to elucidate the underlying mechanisms. Global and/or myeloid cell–specific A2A R‐disrupted mice and control mice were fed a high‐fat diet (HFD) to induce NAFLD. In addition, bone marrow–derived macrophages and primary mouse hepatocytes were examined for inflammatory and metabolic responses. Upon feeding an HFD, both global A2A R‐disrupted mice and myeloid cell–specific A2A R‐defcient mice revealed increased severity of HFD‐induced hepatic steatosis and inflammation compared with their respective control mice. In in vitro experiments, A2A R‐deficient macrophages exhibited increased proinflammatory responses, and enhanced fat deposition of wild‐type primary hepatocytes in macrophage–hepatocyte cocultures. In primary hepatocytes, A2A R deficiency increased the proinflammatory responses and enhanced the effect of palmitate on stimulating fat deposition. Moreover, A2A R deficiency significantly increased the abundance of sterol regulatory element‐binding protein 1c (SREBP1c) in livers of fasted mice and in hepatocytes upon nutrient deprivation. In the absence of A2A R, SREBP1c transcription activity was significantly increased in mouse hepatocytes. Conclusion : Taken together, our results demonstrate that disruption of A2A R in both macrophage and hepatocytes accounts for increased severity of NAFLD, likely through increasing inflammation and through elevating lipogenic events due to stimulation of SREBP1c expression and transcription activity. (Hepatology 2018;68:48‐61).